Complementary Implementation of Sujok on Blood Pressure, Pulse, Respiration, and PONV in Post-Surgical Patients with Spinal Anesthesia - Iqbal Wahyuda; Mardiono, Mardiyono; Ta’adi, Ta’adi; Pujiastuti, Rr. Sri Endang; Arwan, Arwan (Window of Health : Jurnal Kesehatan, 2023)
Spinal anesthesia can cause nausea and vomiting. It is due to the non-depolarizing effect of the drug on the spinal cord, where there are chemoreceptor trigger zone receptors. As much as 53.4% ​​of PONV in gynecological surgery using spinal anesthesia in Indonesia, and at cesarean section 60% in spinal anesthesia. One of the efforts that have been carried out is acupressure, but the incidence of PONV is still relatively high. Another intervention that can overcome PONV is the complementary intervention of sujok. This research aims to analyze the effectiveness of sujok implementation on post-surgical syndrome in patients with spinal anesthesia. This study used a true experiment with a proportional random sampling technique. Data collection involved 32 respondents divided into two groups: control and intervention groups, with 16 samples each. This study used the implementation of sujok given two times in 1 day. There was a statistically significant decrease in systolic pressure with an average decrease of 120.56 mmHg (p= 0.00), diastolic with an average decrease of 75.88 mmHg (p= 0.00), pulse with an average decrease of 71.25 x/minute (p= 0.00), respiration with an average decrease of 17.00 x/minute (p= 0.00), and PONV nausea and vomiting score with the average decrease value became 0.44 (p = 0.00) at the 28-hour observation result after being given implementation. Sujok implementation with a duration of 30 minutes, which is stimulated every 10 minutes for 3 minutes, performed at 1 hour and 24 hours after surgery, effectively reduces systolic pressure, diastolic pressure, pulse, respiration, and PONV.